Forensic Analysis of Wound Healing Biomarkers for Estimating Injury Age in Medico-Legal Cases. A Cross-Sectional Study - Farhat Sultana, Khalid Mahmood, Fariha Tariq, Riasat Ali, Zubia Iqbal, Aatiqa Abbas (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Accurate wound age estimation has a very important value in forensic investigations especially in medico-legal cases. Traditional histopathological methods are subjective and can be limited by inter-individual variability. Recently there have been advances towards molecular biomarkers as an objective alternative. Aims and Objectives: The aim of this study was to quantify wound healing biomarkers expression pattern to accurately estimate injury age in medico legal cases in Pakistan. The aims were to relate biomarker activity to known injury intervals and to develop a predictive framework for forensic applications. Methodology: This is a cross-sectional study of n=80 medico-legal cases with documented injury to a sampling interval of 2 hours to 14 days. Histopathological evaluation and immunohistochemical analysis were performed on tissue samples obtained during autopsies or postmortem forensic examinations. The inflammatory cytokines (IL-6, IL-1β, TNF-α), growth factors (VEGF, TGF-β), and the matrix remodelling enzyme (MMP-9) were key biomarkers that we analyzed. The semi-quantitative scoring of biomarker expression was statistically correlated to injury age by Pearson’s correlation analysis and one-way ANOVA. Results: Progressive changes in cellular infiltration and tissue remodeling were demonstrated in histopathological examination of wound age groups. In early wounds, immunohistochemical findings revealed high expression of inflammatory markers, peak of growth factors in the intermediate phase, and increased MMP-9 in late wounds. The groups were significantly different (p < 0.001) among each other which indicates the temporal correlation between biomarker expression and injury age. Conclusion: A multi-biomarker approach is a feasible, objective, and reliable estimation of wound age, and could be used to improve forensic investigations in Pakistan. Keywords: Wound Age Estimation, Forensic Pathology, Biomarkers, Immunohistochemistry, Medico-Legal, Pakistan